IMPACT OF DIGITAL TECHNOLOGIES ON POVERTY REDUCTION (Scientific electronic journal "Labor Economics and Human Capital", 2024)
In recent years, strategies and programs for reducing poverty have been developed in Uzbekistan, the purpose of which is to increase the standard and quality of life of the population in the regions. This article is devoted to the study of the effective impact of digital technologies in reducing poverty in Uzbekistan. A cross-sectional research design was selected for this study, and the research approach was quantitative, and the methods of data collection consisted of primary and secondary methods. Chi-square test of independence and Mann-Whitney tests were used in the analysis of research results, and all analyzes were performed in SPSS 29.0.1 statistical program. The results of the analysis showed that digital technologies have a positive effect on reducing poverty. At the end of the study, a model for increasing the impact of digital technologies on poverty reduction was proposed.
Keywords: digital technologies, poverty reduction, financial services, e-commerce platforms